2003
DOI: 10.1115/1.1626129
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the Delft University Wind Turbine Dedicated Airfoils

Abstract: This paper gives an overview of the design and wind tunnel test results of the wind turbine dedicated airfoils developed by Delft University of Technology (DUT). The DU-airfoils range in maximum relative thickness from 15% to 40% chord. The first designs were made with the XFOIL code. The computer program RFOIL, which is a modified version of XFOIL featuring an improved prediction around the maximum lift coefficient and the capability of predicting the effect of rotation on airfoil characteristics, has been us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(154 citation statements)
references
References 2 publications
4
147
0
3
Order By: Relevance
“…The classification shows the geometric profile of a NACA aerofoil where the 1st digit refers to maximum chamber to chord ratio, 2nd digit is the camber position in tenths of the chord and the 3rd & 4th digits are the maximum thickness to chord ratio in percent [24]. The emergence of wind turbine specific aerofoils such as the Delft University [23], LS, SERI-NREL and FFA [6] and RISO [26] now provide alternatives specifically tailored to the needs of the wind turbine industry.…”
Section: Aerodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classification shows the geometric profile of a NACA aerofoil where the 1st digit refers to maximum chamber to chord ratio, 2nd digit is the camber position in tenths of the chord and the 3rd & 4th digits are the maximum thickness to chord ratio in percent [24]. The emergence of wind turbine specific aerofoils such as the Delft University [23], LS, SERI-NREL and FFA [6] and RISO [26] now provide alternatives specifically tailored to the needs of the wind turbine industry.…”
Section: Aerodynamicsmentioning
confidence: 99%
“…The co-efficient for the lift and drag of aerofoils is difficult to predict mathematically, although freely available software, such as XFOIL [21] model results accurately with the exception of post stall, excessive angles of attack and aerofoil thickness conditions [22,23]. Traditionally aerofoils are tested experimentally with tables correlating lift and drag at given angles of attack and Reynolds numbers [24].…”
Section: Aerodynamicsmentioning
confidence: 99%
“…A comparison between experimental data provided by Delft University of Technology (DUT) [15] and numerical results is done. The numerical values have been obtained using both, the fine (19 × 10 6 CV) and the coarse (3.9 × 10 6 CV) meshes.…”
Section: The Du-93-w-210 Case Resultsmentioning
confidence: 99%
“…The DU97-Flatback airfoil, a flatback version of the TU-Delft DU97-W-300 airfoil [24], is employed in the present study as the baseline blunt trailing edge airfoil, as shown in Figure 1 with a blue dashed line. The DU97-Flatback airfoil is created by adding thickness symmetrically to the aft 60% of the DU97-W-300 airfoil, giving a blunt trailing edge with a thickness of 10% chord.…”
Section: Description Of CC Airfoil Configurationsmentioning
confidence: 99%